2000
DOI: 10.1897/1551-5028(2000)019<0667:bpopba>2.3.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation Patterns of Polychlorinated Biphenyls and Chlorinated Pesticides in Northwest Atlantic Pilot Whales

Abstract: Abstract-Contaminant exposure is widespread among marine mammals but is of unknown significance. This study characterized organochlorine bioaccumulation in pilot whales, and these bioaccumulation patterns are proposed as representative of Northwest (NW) Atlantic cetacea. Samples were collected from whales stranded in Massachusetts and caught in nets. Polychlorinated biphenyl (PCB) and chlorinated pesticide concentrations were determined via GC/ECD and found to be similar to those reported for other NW Atlantic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 31 publications
0
20
1
Order By: Relevance
“…Squid are known to be a preferred food source of common and white-sided dolphins in the New England area (Weisbrod et al, 2000). Analysis of the squid HOC extract by GCMS-ECNI using SIM showed the presence of all three MBPs discussed herein.…”
Section: Quantitation Of the Uhcsmentioning
confidence: 69%
“…Squid are known to be a preferred food source of common and white-sided dolphins in the New England area (Weisbrod et al, 2000). Analysis of the squid HOC extract by GCMS-ECNI using SIM showed the presence of all three MBPs discussed herein.…”
Section: Quantitation Of the Uhcsmentioning
confidence: 69%
“…In addition, marine mammals have long been recognized as sentinel species. The analysis of data and samples collected from stranded cetaceans and pinnipeds has also provided insights into ocean health (Duignan et al 1996, Weisbrod et al 2000, Nawojchik et al 2003, Shaw et al 2005, Wilson et al 2005, Gulland & Hall 2007, Harper et al 2007, LasekNesselquist et al 2008, Pangallo et al 2008. Data from the [2005][2006] portion of the present study (which covers 2000 to 2006) have been previously reported as part of a survey of live and dead marine mammals, fish, and birds , Lasek-Nesselquist et al 2008.…”
Section: Introductionmentioning
confidence: 78%
“…Blue whales feed exclusively on krill (Breton, 1986), while humpback whales feed heavily on small fish (Borobia, Gearing, Simard, Gearing, & Be´land, 1996;Weisbrod et al, 2000b). The different patterns of PCB congeners and DDT metabolites in blue and humpback whales could reflect differences in the patterns of these contaminants in fish and krill.…”
Section: Discussionmentioning
confidence: 99%
“…Limited data from marine mammals indicate that persistent contaminants partition from the body of females through the placenta into the developing fetus (Gauthier, Pelletier, Brochu, Moore, Metcalfe, & Be´land, 1998;Tanabe, Tatsukawa, Maruyama, & Miyazaki, 1982;Weisbrod, Shea, Moore, & Stegeman, 2000b). Contaminants also partition from the female into maternal milk, which is consumed by the young prior to weaning.…”
Section: Introductionmentioning
confidence: 99%